2015
DOI: 10.1007/s11356-015-4799-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content in vegetables and fruits cultivated in Baia Mare mining area (Romania) and health risk assessment

Abstract: Information about heavy metal concentrations in food products and their dietary intake are essential for assessing the health risk of local inhabitants. The main purposes of the present study were (1) to investigate the concentrations of Zn, Cu, Pb, and Cd in several vegetables and fruits cultivated in Baia Mare mining area (Romania); (2) to assess the human health risk associated with the ingestion of contaminated vegetables and fruits by calculating the daily intake rate (DIR) and the target hazard quotient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 16 publications
8
57
2
1
Order By: Relevance
“…The levels were in the order arugula > spinach > lettuce > tomato > apricot > fig. The higher levels of zinc in this study were noticed in leafy vegetables compared to fruits and fruity vegetable samples, which is consistent with similar notes reported previously (Roba et al 2015). Zinc is considered as an essential plant micronutrient, and it has a long biological half-life in plants (Nagajyoti et al 2010).…”
Section: Zincsupporting
confidence: 92%
“…The levels were in the order arugula > spinach > lettuce > tomato > apricot > fig. The higher levels of zinc in this study were noticed in leafy vegetables compared to fruits and fruity vegetable samples, which is consistent with similar notes reported previously (Roba et al 2015). Zinc is considered as an essential plant micronutrient, and it has a long biological half-life in plants (Nagajyoti et al 2010).…”
Section: Zincsupporting
confidence: 92%
“…This paper, the final part of a complex three-part work, aims to present the consequences of air pollution on public health in Baia Mare between 1980 and 2006. Our work brings up to date and enlarges the bulk of information provided by the very few papers that cover the subject of air pollution effects on public health in Baia Mare (Lacatusu et al, 1996;Dobra and Viman, 2006;Nadisan, 2006;Jelea and Jelea, 2007;Oroian, 2010;Roba et al, 2016;Smical, Muntean and Torok, 2016). In a previous paper, the first of this series, we presented an overview of historical air pollution sources in Baia Mare .…”
Section: Purpose Of the Study And Backgroundmentioning
confidence: 81%
“…National Standard of the People's Republic of China (2012) set the maximum levels of Cr and Ni in foods were 0.5 mg/kg and 1.0 mg/kg, respectively. Meanwhile, maximum level of Cu in fruit was 5 mg/kg according to Romanian Ministry of Agriculture Food and Forestry Order (Roba et al, 2016). The results showed that the levels of Cr, Cu, and Ni in commercially snake fruit samples were acceptable.…”
Section: Determination Of CD Cr Cu Ni and Pb In Snake Fruitmentioning
confidence: 94%
“…Based on LoD values, ICP-AES was sensitive enough for analysis of these heavy metals because LoD values were lower than maximum values of heavy metals allowed to be present in fruit products, i.e. 0.5 µg/g (Roba et al, 2016).…”
Section: Validation Of Icp-aesmentioning
confidence: 99%